2021
DOI: 10.3310/hta25240
|View full text |Cite
|
Sign up to set email alerts
|

Microdiscectomy compared with transforaminal epidural steroid injection for persistent radicular pain caused by prolapsed intervertebral disc: the NERVES RCT

Abstract: Background Sciatica is a common condition reported to affect > 3% of the UK population at any time and is most often caused by a prolapsed intervertebral disc. Currently, there is no uniformly adopted treatment strategy. Invasive treatments, such as surgery (i.e. microdiscectomy) and transforaminal epidural steroid injection, are often reserved for failed conservative treatment. Objective To compare the clinical effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…A recent randomised controlled trial compared surgical microdiscectomy with TFESI (transforaminal ESI) in patients with disc-related sciatica pain with symptom duration of up to 12 months. 15 No significant difference was found for pain or disability outcomes, and the trial team recommended that TFESI should be considered as a first invasive treatment option. With the need to reduce low-value healthcare, 16 it would be helpful to be able to better identify patients who have a reasonable chance of benefiting from ESI.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent randomised controlled trial compared surgical microdiscectomy with TFESI (transforaminal ESI) in patients with disc-related sciatica pain with symptom duration of up to 12 months. 15 No significant difference was found for pain or disability outcomes, and the trial team recommended that TFESI should be considered as a first invasive treatment option. With the need to reduce low-value healthcare, 16 it would be helpful to be able to better identify patients who have a reasonable chance of benefiting from ESI.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Anecdotally, we know clinicians use the “flip of a coin” analogy, that is, explaining to patients that they have a “50:50” chance of improvement from an ESI. A recent randomised controlled trial compared surgical microdiscectomy with TFESI (transforaminal ESI) in patients with disc-related sciatica pain with symptom duration of up to 12 months 15. No significant difference was found for pain or disability outcomes, and the trial team recommended that TFESI should be considered as a first invasive treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…In a large cohort of patients that were randomized to either receive epidural steroid injections or not, as well as randomized to either undergo discectomy or not, a significantly greater percentage (41%) of those in the surgical group that received epidural steroid injection crossed over to the nonsurgical group, compared to those in the surgical group that had not undergone steroid injection (19%), acknowledging that the baseline preference for surgery was higher in the nonsteroid group. 40 Another study randomized 163 patients with radicular low back pain due to disc herniation to receive epidural steroid injection or microdiscectomy, and found no significant difference between the two treatment modalities in terms of pain reduction or disability reduction 41 These interventions are not without downside. The inclusion of steroid into an epidural injection can also introduce the systemic effects of steroid to the body, even without it being administered intravascularly.…”
Section: Lumbar Epidural Steroid Injectionmentioning
confidence: 99%
“…Several recent studies have examined options for the management of lumbar disc herniation. In a randomized controlled trial, Wilby et al compared microdiscectomy with transforaminal epidural corticosteroid injection in patients with persistent radicular pain for <1 year secondary to disc herniation 12 . The authors found that there were no significant differences in pain scores between the epidural injection group and the surgery group, although 18% of the injection group underwent a surgical procedure prior to the completion of the study.…”
Section: Lumbar Disc Herniation and Lumbar Degenerative Conditionsmentioning
confidence: 99%